Mapeamento do estado nutricional, produtividade e qualidade de bebida do café conilon - Fonseca, Abel Souza da (2018)
Brazil accounts for about one third of the world coffee production, making it the largest producer and exporter of coffee. The localities where coffee is grown have a great diversity of edaphoclimatic characteristics, allowing the cultivation of several g